Significance of nailfold videocapillaroscopy in patients with idiopathic inflammatory myopathies. (28th August 2018) - Kubo, Satoshi; Todoroki, Yasuyuki; Nakayamada, Shingo; Nakano, Kazuhisa; Satoh, Minoru; Nawata, Aya; Satoh, Yurie; Miyagawa, Ippei; Saito, Kazuyoshi; Smith, Vanessa; Cutolo, Maurizio; Tanaka, Yoshiya
Abstract: Objective: The aim of this study was to investigate the clinical and immunological significance of nailfold videocapillaroscopy (NVC) abnormalities in patients with idiopathic inflammatory myopathies (IIMs). Methods: Seventy consecutive Japanese patients with untreated IIMs, enrolled between April 2014 and August 2017, were prospectively studied. Clinical features, NVC findings, autoantibody profile by immunoprecipitation and ELISA, and histopathological findings of skin biopsies of DM rash were assessed at baseline and after 1-year of immunosuppressive therapy. Results: NVC abnormalities were found in 55.7% (39/70) of IIM patients, with significantly higher prevalence in DM (65.4%) compared with PM (27.8%) ( P = 0.01). In subsets of patients classified by autoantibody specificities, the prevalence of NVC abnormalities was significantly higher in patients with anti-MDA5 (87.5%) and anti-transcriptional intermediary factor 1γ (88.9%) vs anti-aminoacyl-tRNA synthetase (26.9%, P < 0.001). Perivascular lymphocytic infiltration in the upper dermis of skin rash biopsy of DM was more severe in patients with NVC abnormalities ( P < 0.05). Unexpectedly, NVC abnormalities disappeared in 75% of IIM patients after 1-year of immunosuppressive therapy in contrast to stable NVC changes seen in scleroderma patients. Conclusion: Nailfold microvascular abnormalities were common in DM patients, associated with anti-MDA5 and transcriptional intermediary factor 1γ antibodies, and perivascular inflammation in skin histology. NVC abnormalities in IIMs may become clinically useful markers for defining subsets of DM and understanding the pathogenesis of the clinical features seen in these patients.